Krimić kao literatura. "Biografija utopljenice" Branka Belana između egzistencijalizma i popularne književnosti - Grdešić, Maša (Array, 2006)
While Belan's novel "Biography of a Drowned Woman", a hard-boiled crime novel close to film noir tradition, blends crime fiction with existentialist literature, the link between crime fiction and high literature is made even clearer in Viktor Žmegač's and Zdenko Škreb's books on popular literature.